Customer Focus in Banking Services - Sebastian Titus, A.P.; Lawrence, Albin D. Robert (Indian Journal of Marketing, 2004)
As the intense competition becomes a way of doing business, it is the customer who calls the shot in deciding the nature of products and services offered in the market. The customers are becoming demanding, dominant and selective. In fact, the perceptions and the expectations of the customers have undergone a sea change; with the availability of the banking services to the customers at their doorsteps through the help of technology. Now days, they have also become more immune to marketer’s pressure1 This means That the advertising and marketing gimmicks will work only when they see real quality in the provision of services at the ground level. Marketing of banking services would imply creation and delivery of customer satisfying services at a profit to the bank. IT is the mix of six P’s- price, place, promotion, people and procedures.